Estudo de tenacidade da zona termicamente afetada dos aços inoxidáveis ferríticos UNS S41001 e UNS S41003 - Alberto Hisashi Hibino (2011)
This study aimed to characterize of toughness of heat affected zone (HAZ) produced by Gas Metal Arc Welding (GMAW) in two ferritic stainless steels, UNS S40910 and UNS S41003, both at approximately 6.5 mm thick. These samples were obtained from industrial scale hot rolled intermediate plates. One of them was annealed before been used in the present study. Welding was performed in 2 energy levels, using an AWS SFA 5.9 E308 LSi with 1.2 mm in diameter filler wire. The analysis was aided by thermal cycle curves determined by mathematical models. The samples were evaluated by metallography, microhardness measurement, fractography and mechanical testing including Charpy testing and Crack Tip Opening Displacement (CTOD) testing to determine the toughness of HAZ. The results were used to compare the two steels, one stabilized with Ti and the other without stabilization, in two welding energies. The HAZ of both steels were embrittled probably by grain growth in both steels and by martensite formation in the S41003 steel